Azerbaijan-Türkiye Relations in the Context of Security Community: One Nation, Two States - Zehra Karayel (Güvenlik Stratejileri Dergisi)
The cooperative relations between Türkiye and Azerbaijan have benefitted them in recent years individually and collectively; they have developed and pursued collective interests. This study aims to discover the nature of the relationship between Türkiye and Azerbaijan in the context of the security community. With the expanding brotherly relations among the people, the two countries created a common entity similar to what Karl Deutsch called a “security community”. Constructivist scholars Adler and Barnett brought some path-dependent variables and classifications to the concept of the security community, making research on this subject easier to conduct. This paper will evaluate the recent developments between the two countries using the case analysis method in light of the criteria these security community theorists developed and determine its place in security community classification. It will argue that the relationship qualifies a mature security community as cooperation created common goals and interests that bound them together and developed mutual trust and identity. The paper will contribute to the literature on the security community and the countries’ foreign policy.